Renegotiation of subject content: interpretations of new art education policy - Ahrenby, Hanna (Scandinavian journal of educational research, 2025)
Subject matter development in education is a highly complex process. Previous studies indicate that time limitations, diversity of subject matter, and goal-oriented management of schools can exacerbate difficulties in selecting content in compulsory school-level education. This study addresses aspects that have received less attention: the formation of subject content (through renegotiation and interpretation of changing policies) in an illustrative school subject (Art) that is not aligned with a specific academic discipline. For this purpose, I have analyzed policy documents and expressions of interviewed art teachers and officials using Bernstein’s pedagogical device theory. The results indicate that absence of an affiliation with an academic discipline facilitates changes in subject content. Furthermore, the renegotiation of policy (and hence subject content) are strongly influenced by societal changes and ideologies in the official recontextualization field, while the strong internal classification of the Art subject significantly influences content selection in the pedagogical recontextualization field.